Creating Supportive EFL Classrooms for Diverse Students of Ecuador - Espinosa Cevallos, Ligia F. (2017)
Diversity affects the way the students learn, and in some circumstances, this diversity even disrupts the learning process. Thus, EFL teachers need to use diverse teaching strategies to provide their students a rigorous, relevant, complex, varied, and flexible instruction that benefits all types of learners. This paper seeks to understand five important sources of diversity found in EFL classrooms in Ecuador in order to determine which strategies are effective to address students’ individual needs, and how these strategies can improve education as a whole in Ecuador.